2018
DOI: 10.3390/ijms19082169
|View full text |Cite
|
Sign up to set email alerts
|

Identification of WRKY Gene Family from Dimocarpus longan and Its Expression Analysis during Flower Induction and Abiotic Stress Responses

Abstract: Longan is an important fruit tree in the subtropical region of Southeast Asia and Australia. However, its blooming and its yield are susceptible to stresses such as droughts, high salinity, and high and low temperature. To date, the molecular mechanisms of abiotic stress tolerance and flower induction in longan have not been elucidated. WRKY transcription factors (TFs), which have been studied in various plant species, play important regulatory roles in plant growth, development, and responses to stresses. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 69 publications
(108 reference statements)
0
29
0
Order By: Relevance
“…According to classifications in the WRKY family [18,28,75], WRKY12 belongs to Group IIc and contains a single WRKY domain and a CX4-5CX22-23HXH zinc-finger motif. Recent studies have shown that the WRKYGQK heptapeptide, which can specifically recognize and bind to the W-box consensus sequence (TTGACY) in the promoters of target genes, can be replaced by WRKYGKK, WRKYGEK, WKKYEDK, or WKKYCEDK; variations of the WRKYGQK motif might change the DNA binding specificities to downstream target genes [75]. However, multiple sequence alignment results showed that WRKY12 in different species only harbor the same WRKYGQK heptapeptide, demonstrating that WRKY12 protein is evolutionarily conserved and can recognize and bind to downstream target genes (Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…According to classifications in the WRKY family [18,28,75], WRKY12 belongs to Group IIc and contains a single WRKY domain and a CX4-5CX22-23HXH zinc-finger motif. Recent studies have shown that the WRKYGQK heptapeptide, which can specifically recognize and bind to the W-box consensus sequence (TTGACY) in the promoters of target genes, can be replaced by WRKYGKK, WRKYGEK, WKKYEDK, or WKKYCEDK; variations of the WRKYGQK motif might change the DNA binding specificities to downstream target genes [75]. However, multiple sequence alignment results showed that WRKY12 in different species only harbor the same WRKYGQK heptapeptide, demonstrating that WRKY12 protein is evolutionarily conserved and can recognize and bind to downstream target genes (Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…PUB proteins play important roles in regulating plant growth and development [34]. In the present study, the 29 MaU-box genes (MaU-box3/4/8/9/10/13/17/18/19/20/22/25/27/28/34/38/39/41/43/48/49/50/51/52/56/59/61/63/70) had the highest expression at the beginning of banana’s developmental stage (day 25), which could be explained by the fact that the highly expressed genes usually play important roles in plant development [35], suggesting ubiquitination activation through the first stages of fruit development. Of note, the expression of eight MaE2 genes [23] and three MaU-box genes decreased gradually with prolonged developmental time.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the D. longan roots and leaves are also used as traditional Chinese herbal medicine, but are not widely applied due to the little accumulation of flavonoids and other important secondary metabolites. Furthermore, the circumstance (e.g., high temperature) where the D. longan usually grows was another important factor adversely affecting their qualities and yields (Jue et al, 2018). Studies have shown that the biosynthesis of flavonoids, a complex biological process, is regulated by the WD40 TF family in plants (Liu et al, 2013).…”
Section: Protein-protein Interactionsmentioning
confidence: 99%
“…Our previous studies suggested that the 4 bZIP genes that were differently expressed between D. longan roots and leaves might be involved in the secondary metabolite accumulations (Zheng et al, 2020). In D. longan, the up-regulated expressions of WRKY1, WRKY8, and WRKY50 correspondingly contributed to the tolerance to drought, heat, and cold stresses, respectively (Jue et al, 2018). Therefore, it is urgent to investigate the key TF which not only participate in flavonoid biosynthesis but also enhance abiotic resistances.…”
Section: Introductionmentioning
confidence: 99%